Price behaviour of major vegetables in hill region of nepal: an econometric analysis (SAARC Journal of Agriculture, 2014)
An attempt has been made to study the price behaviour of major vegetables in hill region of Nepal. The study is based on secondary data on wholesale monthly/weekly arrivals and prices for the period of 2000-01 to 2009-10. The seasonality in wholesale price was analyzed using multiplicative model; the Fourier analysis was used to analyze cyclical variation in wholesale prices and Autoregressive model to study the relationship between market arrival and price of vegetables in market of hill region of Nepal. It was found that during the post-harvest period, the wholesale price ruled very low while during the lean period, the prices were quite high which is due to seasonal and perishable nature of the vegetables. The entire vegetables registered the positive and increasing trend and periodicities of 2 to 3 years in the wholesale price of vegetables. The effect of lagged price on current wholesale price was positively significant and high in magnitude and significant negative response was observed for the relationship between wholesale price and market arrival for all the vegetables in the market of hill region. Therefore, improved market information system is a need of efficient vegetable markets in Nepal in order to enable farmers to make proper production and marketing decisions. Further, Government is required to create market infrastructure facilities like warehousing, processing, transportation, etc. for reducing the variation in prices of vegetables in the market of hill region of Nepal. DOI: http://dx.doi.org/10.3329/sja.v10i2.18332 SAARC J. Agri., 10(2): 107-120 (2012)